The validity of incremental exercise testing in discriminating of physiological profiles in elite runners - Legaz Arrese, Alejandro; Munguía Izquierdo, Diego; Carranza García, Luis Enrique; Reverter Masía, Joaquín; Torres Dávila, Celeste Guadalupe; Medina Rodríguez, Rosa Elena (Akadémiai Kiadó, 2011)
The goal of this study was to determine whether traditional ergoespirometric incremental exercise testing carried out to the point of exhaustion could be useful in distinguishing the physiological profiles of elite runners that compete in races that lasted about 8 minutes versus those that lasted about 2 hours. Ten male marathon runners (performance time: 2:12:04, coefficient of variation (CV) = 2.33%) and 8 male 3000 m steeplechase runners (performance time: 8:37.83, CV = 2.12%) performed an incremental test on the treadmill (starting speed 10 km. h–1; increments, 2 km. h–1; increment duration, 3 min to exhaustion). Heart rate (HR), VO2 , and lactate concentrations were measured at the end of each exercise level. At maximal effort, there were no differences between the groups regarding VO2max and maximal HR; however, the workload time, vVO2max and peak treadmill velocity were significantly higher in the 3000 m steeplechase group (p<0.05). At submaximal effort, there were no significant differences between groups for VO2(ml.kg–1.min–1), HR, or lactate. Our results show that this type of testing was not sufficient for discriminating the physiological profiles of elite runners who competed in middle-distance versus long-distance events (e.g. in the marathon and the 3000 m steeplechase).